Volkswagen South Africa : VW up! marketing - Saini, Yvonne; Townsend, Stephanie (London : Wits Business School, 2016)
At the beginning of August 2016, Bridget Harpur, marketing brand manager for Volkswagen Group South Africa (VWSA), and Mark Handley, national sales manager, were debating how to grow sales of the entry-level VW up! that VWSA had launched in February 2015. The entry-level passenger car category was relatively small and highly competitive. The VW up! was VWSA's first car ever to target this market category. The car had maintained an average 8.5% market share since its launch. Handley and Harpur believed it had potential to build this share, especially among young, urban drivers. The question was how to adjust the communication strategy to capture the attention of this market.
Originally published in Saini, Y., & Townsend, S. (2016). Volkswagen South Africa: VW up! Marketing. WBS-2016-15. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Harpur, Bridget; Handley, Mark; Volkswagen Kommunikation; Automobiles -- Marketing